The Impact of Coping Style on Gaze Duration - Klucken, Tim; Brouwer, Anne-Marie; Chatziastros, Astros; Kagerer, Sabine; Netter, Petra; Hennig, Juergen (PloS one, 2010)
The understanding of individual differences in response to threat (e.g., attentional bias) is important to better understand the development of anxiety disorders. Previous studies revealed only a small attentional bias in high-anxious (HA) subjects. One explanation for this finding may be the assumption that all HA-subjects show a constant attentional bias. Current models distinguish HA-subjects depending on their level of tolerance for uncertainty and for arousal. These models assume that only HA-subjects with intolerance for uncertainty but tolerance for arousal ("sensitizers") show an attentional bias, compared to HA-subjects with intolerance for uncertainty and intolerance for arousal ("fluctuating subjects"). Further, it is assumed that repressors (defined as intolerance for arousal but tolerance for uncertainty) would react with avoidance behavior when confronted with threatening stimuli. The present study investigated the influence of coping styles on attentional bias. After an extensive recruiting phase, 36 subjects were classified into three groups (sensitizers, fluctuating, and repressors). All subjects were exposed to presentations of happy and threatening faces, while recording gaze durations with an eye-tracker. The results showed that only sensitizer showed an attentional bias: they gazed longer at the threatening face rather than at the happy face during the first 500 ms. The results support the findings of the relationship between anxiety and attention and extend these by showing variations according to coping styles. The differentiation of subjects according to a multifaceted coping style allows a better prediction of the attentional bias and contributes to an insight into the complex interplay of personality, coping, and behavior.